Analisis Kurikulum Sekolah Dasar Islam Sebagai Upaya Mencetak Generasi Berkarakter - Anisa, Nur Sya’ban; Isabela, Isabela; Huda, Almas Noor; Hamel, Sabhine Octaviani; Rahayu, Erni; Yuniarti, Yeni; Sukardi, Rendi Restiana (Education and Development Research, 2023)
Abstract: Each school has its curriculum, and SD Prasetiya Bangsa Islamic School is no exception, which is located in Purworejo Regency, Central Java. The research was conducted to find out how the process of implementing the curriculum implemented by SD Prasetiya Bangsa Purworejo Islamic School as an Islamic-based private elementary school is in forming the next generation with character. In the process, researchers used a case study method with a qualitative descriptive approach. Instruments were used in the form of interviews, observation, and documentation. Data processing was carried out using interactive analysis techniques, namely data collection, data reduction, data presentation, and conclusion. The research results obtained, SD Prasetiya Bangsa Islamic School uses 3 curriculum combinations which include international, national (2013 curriculum), and Islamic curriculum in its efforts to create a generation of character. In practice, habituation and leadership as well as 4C skills (Critical Thinking, Communication, Creativity, and Collaboration) are very much considered in daily activities. In addition to educating children in their activities at school, the Elementary School also cooperates well with parents of students through parenting classes to unite perceptions in educating children with character so that the efforts made by both parties are in synergy. Abstrak: Setiap sekolah memiliki kurikulumnya masing-masing tidak terkecuali SD Prasetiya Bangsa Islamic School yang terletak di Kabupaten Purworejo, Jawa Tengah. Penelitian dilakukan untuk mengetahui bagaimana proses pelaksanaan kurikulum yang diterapkan oleh SD Prasetiya Bangsa Purworejo Islamic School sebagai Sekolah Dasar (SD) swasta berbasis islam dalam membentuk generasi penerus yang berkarakter. Pada prosesnya, peneliti menggunakan metode studi kasus dengan pendekatan deskriptif kualitatif. Instrumen yang digunakan berupa wawancara, observasi, dan dokumentasi. Pengolahan data dilakukan dengan teknik analisis interaktif, yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian yang diperoleh, SD Prasetiya Bangsa Islamic School menggunakan 3 kombinasi kurikulum yang meliputi kurikulum internasional, nasional (kurikulum 2013), dan kurikulum islam dalam upayanya mewujudkan generasi berkarakter. Dalam praktiknya, pembiasaan dan leadership serta kemampuan 4C (Critical Thinking, Communication, Creativity, and Collaboration) sangat diperhatikan dalam aktivitas keseharian. Selain mendidik anak dalam aktivitasnya di sekolah, pihak Sekolah Dasar juga menjalin kerja sama yang baik dengan wali murid melalui kelas parenting untuk menyatukan persepsi dalam mendidik anak yang berkarakter supaya usaha yang dilakukan kedua belah pihak saling bersinergi.